The Destruction of the Accountability of Federal Officials for Constitutional Torts - Robert Roberts (Public Administration Quarterly, 2026)
The manuscript seeks to determine whether constitutional tort lawsuits against federal executive-branch public administrators constitute an effective remedy for such administrators’ unconstitutional conduct. The article also seeks to answer whether plaintiffs alleging mistreatment of federal law enforcement officers and agents may invoke the Federal Tort Claims Act (FTCA) to hold them accountable for unconstitutional conduct. The examination of constitutional tort jurisprudence applicable to the conduct of federal executive-branch public administrators finds that the U.S. Supreme Court has effectively barred so-called Bivens constitutional tort actions against them. The manuscript argues that the U.S. Supreme Court’s constitutional tort jurisprudence has had a direct impact on efforts by the second Trump administration to sharply increase the number of deportations of immigrants without legal authorization to reside in the United States. This has left victims of unconstitutional conduct by ICE agents without the ability to recover monetary damages for their mistreatment. Finally, the manuscript argues that academic public administration has paid insufficient attention to situations in which federal public administrators openly violate the rule of law and invoke utilitarian moral reasoning to justify their actions. Academic public administration provides explanations for such behavior by examining administrative evil and utilitarian moral reasoning. Academic public administration, however, has failed to provide a remedy for a growing number of bureaucrats who refuse to embrace higher-order moral values and turn their backs on deontological moral reasoning.